Topics in American art since 1945 : Abstract expressionism, Hard edge and systems, Conceptual art, Pop art, Happenings, Earthworks, Public sculpture, The changing role of the critic. - Alloway, Lawrence (New York : W.W. Norton & Company New York, 1975)
Andre, Carl ; Arakawa, Shusaku ; Artschwager, Richard ; Baziotes, William ; Bechtle, Robert ; Bluhm, Norman ; D'Arcangelo, Allan ; Dine, Jim ; Feeley, Paul ; Goings, Ralph ; Gorky, Arshile ; Gottlieb, Adolph ; Huebler, Douglas ; Johns, Jasper ; Kaprow, Allan ; Katz, Alex ; de Kooning, Willem ; LeWitt, Sol ; Lichtenstein, Roy ; Martin, Agnes ; Morley, Malcolm ; Morris, Robert ; Newman, Barnett ; Noland, Kenneth ; Nutt, Jim ; Oppenheim, Dennis ; Polk Smith, Leon ; Pollock, Jackson ; Rauschenberg, Robert ; Rosenquist, James ; Rothko, Mark ; Ruscha, Ed ; Segal, George ; Sleigh, Sylvia ; Smithson, Robert ; Stamos, Theodoros ; Stella, Frank ; Still, Clyfford ; Thiebaud, Wayne ; Warhol, Andy ; Wesselmann, Tom
Engels
boek
Keywords: U.S.A.; Verenigde Staten